2021
DOI: 10.18388/abp.2020_5959
|View full text |Cite
|
Sign up to set email alerts
|

Towards understanding the novel adhesin function of Candida albicans phosphoglycerate mutase at the pathogen cell surface: some structural analysis of the interactions with human host extracellular matrix proteins

Abstract: Although many atypical proteinaceous cell wall components that belong to a group of multitasking, "moonlighting" proteins, have been repeatedly identified in numerous pathogenic microorganisms, their novel extracellular functions and secretion mechanisms remain largely unrecognized. In Candida albicans, one of the most common fungal pathogens in humans, phosphoglycerate mutase (Gpm1) - a cytoplasmic enzyme involved in the glycolysis pathway - has been shown to occur on the cell surface and has been identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 54 publications
4
8
0
Order By: Relevance
“…Recently, Satala et al. (2021) identified ribosomal protein L10a in the cell wall proteins of C. albicans by LC‐MS/MS analysis, and their results support our findings. Further studies are necessary to identify it and clarify the function of surface‐localized L10a using a recombinant version of it.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Recently, Satala et al. (2021) identified ribosomal protein L10a in the cell wall proteins of C. albicans by LC‐MS/MS analysis, and their results support our findings. Further studies are necessary to identify it and clarify the function of surface‐localized L10a using a recombinant version of it.…”
Section: Discussionsupporting
confidence: 89%
“…Several ribosomal proteins were demonstrated to be localized on the surface of pathogens (Singh et al, 2002;Spence & Clark, 2000). Recently, Satala et al (2021) In conclusion, we demonstrated that C. albicans binds to DMBT1…”
Section: Localization Of the Binding Inhibitory Component On The Surf...supporting
confidence: 50%
“…Much less characterized are fungal surface‐exposed proteins classified into a group of multitasking “moonlighting” proteins (Chaffin et al, 1998). They are represented by originally cytosolic proteins, involved in basic metabolic processes within the cell (Satala, Satala, et al, 2021; Satala, Zelazna, et al, 2021), such as enolase, but also in cell wall remodeling during cell division and yeast‐to‐mycelium transition (Reyna‐Beltrán et al, 2018). However, after secretion into the extracellular environment and further readsorption on the fungal cell surface, they serve as novel adhesion platforms and strongly interact with human cells and selected proteins (Karkowska‐Kuleta et al, 2021; Satala et al, 2020), although their secretion pathways remain enigmatic since they do not possess any signaling sequences (Karkowska‐Kuleta & Kozik, 2014).…”
Section: Albicans Virulence Propertiesmentioning
confidence: 99%
“…Candida species belonging to the CTG clade have evolved multiple virulence factors that are used at different stages of infection in interactions with host proteins and cells and in the evasion of the immune system. Although the set of virulence factors differs within the CTG clade and their expression depends on the type of strain and the stage of infection [31], they involve primarily the production of different classes of proteins, including adhesins and a wide spectrum of hydrolytic enzymes (Figure 2) [32][33][34][35]. Comparative genomic analyses indicated that for C. albicans, a significant enrichment compared to nonpathogenic yeasts was found for genes encoding secreted proteases and lipases, acid sphingomyelinases, cytochromes P450, and various transporters.…”
Section: Virulence Of Candida Pathogenic Fungimentioning
confidence: 99%
“…In addition to classic adhesive proteins, this function is also performed by some cytosolic proteins, called moonlighting proteins, and located on the surface of yeast cells, where they perform completely different functions than at the primary location [44,45]. For example, C. albicans cell wall-associated glyceraldehyde-3-phosphate dehydrogenase (Tdh3), an enzyme originally involved in the glycolysis pathway, has a high affinity for extracellular matrix (ECM) components such as fibronectin and laminin [46] or other glycolytic enzymes, phosphoglycerate mutase 1 (Gpm1) which allows adhesion to umbilical vein endothelial cells (HUVEC) and keratinocytes (HaCaT) [47] and to vitronectin and fibronectin [35] and triosephosphate isomerase (Tpi1), which interact with several ECM proteins [48]. C. albicans enolase (Eno1) was also indicated as an abundant moonlighting protein responsible for binding of human high-molecular-weight kininogen (HK), prekallikrein, coagulation factor XII, and plasminogen [34,49,50].…”
Section: Virulence Of Candida Pathogenic Fungimentioning
confidence: 99%